How Is Environmental Performance Associated with Economic Growth? A World Cross-country Analysis - Neagu, Olimpia; Ardelean, Doru Ioan; Lazăr, Vasile (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2017)
The aim of the paper is to explore the association between environmental performance and income level in the world economy in 2016. Data from Yale University and World Bank are used in a cross-country regression analysis comprising 166 countries. The gross Domestic Product per capita (based in purchased power parity, constant 2011 international dollars) in these countries is positively associated with the environmental performance index (EPI) calculated by Yale and Columbia University in 2016. Furthermore, the causality of this relationship is from GDP per capita to Environmental Performance and both Environmental Health (EH) and Ecosystem Vitality (EV) are positively associated with GDP per capita. Environmental Health (EH) is stronger related to GDP per capita, meaning that investments in public health, sanitation and infrastructure are increasing as countries develop.